Difficulty Analysis of Mathematical Problem Solving in Accordance with Student Dependent Fields Based on Marzano Taxonomy for Grade VIII Students - Prasetya, Yulian Rakhel; Mulyono, Mulyono; Rochmad, Rochmad (Unnes Journal of Mathematics Education Research, 2019)
Cognitive style is an individual characteristic in using cognitive function (solving problems). One of the widely studied cognitive styles are field dependent cognitive style and field independent cognitive style. Nowadays problem solving abilities are important to our life. Student difficulties in solving problems is very various. Students low abilities can be seen from how many students make the mistakes in solving the problems. Marzano Taxonomy is developed to break the limitation of Bloom Taxonomy. Marzano Taxonomy cognitive level can be divided into four components retrieval, comprehension, analysis, and utilization. The purpose of this observation is analyse the mathematics problem solving according to level cognitive Marzano Taxonomy viewed from students field dependent cognitive style and students field independent cognitive style.This observation was conducted with qualitative method. Population of this observation is 7th grade students from Junior High School 1 Donorojo Jepara District. The observation sampling technique is cluster random sampling which is random sampling. Based on the results of the research and discussion above, it was found tha t:1)the difficulties experienced by students with the Field Dependent cognitive style in solving mathematical problems based planning. 2).Students with the Field Dependent cognitive style lack the courage to solution. This observation was conducted with qualitative method. Population of this observation is 7th grade students from Junior High School 1 Donorojo Jepara District. The observation sampling technique is cluster random sampling which is random sampling. Based on the results of the research and discussion above, it was found tha t:1)the difficulties experienced by students with the Field Dependent cognitive style in solving mathematical problems based planning. 2). students with the Field Dependent cognitive style lack the courage to solution.3). )the difficulties experienced by students with the Field Independent cognitive style in solving mathematical problems based.4). students with the Field Independent cognitive style don’t have the courage to solution.